Relationships of omega-3 and omega-6 polyunsaturated fatty acids with esophageal diseases: a two-sample Mendelian randomization analysis - Chen, Weiming; Chen, Maohui; Huang, Jin; Xie, Qichang; Huang, Yizhou; Chen, Chun; Zhu, Yong (Frontiers in Nutrition, 2024)
Omega-3 polyunsaturated fatty acids (PUFAs) have been widely studied and used as nutritional supplements because of their anti-inflammatory effects. Previous studies have shown an association between polyunsaturated fatty acids such as omega-3 and omega-6 PUFAs with the development of malignant tumors. However, the relationships of omega-3 and omega-6 PUFAs with esophageal diseases have not been characterized. Mendelian randomization (MR) is a statistical method for identifying instrumental variables (IVs) from genome-wide association study (GWAS) data, and is associated with little confounding by environmental or other disease-related factors. We used genome-wide association study (GWAS) data from previously published studies on circulating concentrations of omega-3, omega-6, docosahexaenoic acid (DHA) and linoleic acid(LA), as well as esophageal cancer and other esophageal diseases, which were downloaded from the IEU OpenGwas database (https://gwas.mrcieu.ac.uk/) and the GWAS Catalog database ( https://www.ebi.ac.uk/). The inverse variance-weighted approach was used as the principal analysis, and the MR-Egger and weighted median methods were used alongside. A series of sensitivity analyses were used to ensure the robustness of the causality estimates. We found that the circulating omega-3 PUFAs concentration was positively associated with esophageal cancer (p=8×10-4), and circulating DHA concentration (the main component of omega-3 in food), was also positively associated with esophageal cancer (p=2×10-2), but no significant association was found between circulating omega-6 PUFAs and esophageal cancer (p=0.17), and circulating LA concentration (the main component of omega-6 in food), was also no significant associated with esophageal cancer(p=0.32). We found no significant relationships of circulating omega-3 and omega-6 PUFAs concentration with four other esophageal diseases. This study indicates that higher levels of circulating omega-3 PUFAs and DHA concentrations may be a risk factor for the development of esophageal cancer. Conversely, an increased omega-6/omega-3 ratio may serve as a protective factor against esophageal cancer. These findings have significant implications for the clinical application of omega-3 PUFAs and the prevention and treatment of esophageal cancer.